Scanning life's matrix genes, proteins, and small molecules - Stuart L. Schreiber, lecturer; Eric S. Lander, lecturer; Ann DeStefano Sutherland, producer; Wally Ashby, director (Howard Hughes Medical Institute, 2003)
Four lectures on genomic science and chemical genetics, with emphasis on how molecular biology, robotics, and advanced computation are combining to characterize a new generation of biomedical research.